2016
DOI: 10.1289/ehp.1509693
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Chemicals in Urine and Blood: Improving Methods for Creatinine and Lipid Adjustment

Abstract: BackgroundInvestigators measuring exposure biomarkers in urine typically adjust for creatinine to account for dilution-dependent sample variation in urine concentrations. Similarly, it is standard to adjust for serum lipids when measuring lipophilic chemicals in serum. However, there is controversy regarding the best approach, and existing methods may not effectively correct for measurement error.ObjectivesWe compared adjustment methods, including novel approaches, using simulated case–control data.MethodsUsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
259
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 370 publications
(261 citation statements)
references
References 12 publications
2
259
0
Order By: Relevance
“…Fourth, we modeled the most meaningful food intake predictors categorically (< 50, 50–99, 100–149,150–199, and ≥200 g) instead of continuously to demonstrate the dose-response relationship. Fifth, we fitted models with metabolite concentrations expressed as nmol/L urine adjusted for creatinine concentration as a separate covariate (O’Brien et al, 2015). Finally, we investigated whether the results were the same if missing confounder values were excluded rather than imputed.…”
Section: Methodsmentioning
confidence: 99%
“…Fourth, we modeled the most meaningful food intake predictors categorically (< 50, 50–99, 100–149,150–199, and ≥200 g) instead of continuously to demonstrate the dose-response relationship. Fifth, we fitted models with metabolite concentrations expressed as nmol/L urine adjusted for creatinine concentration as a separate covariate (O’Brien et al, 2015). Finally, we investigated whether the results were the same if missing confounder values were excluded rather than imputed.…”
Section: Methodsmentioning
confidence: 99%
“…We modeled phenol biomarker concentrations accounting for urinary dilution using a Bayesian modification of the covariate-adjusted creatinine standardization approach described by O’Brien et al (O'Brien and others 2015). We modeled natural log creatinine as a random normal variable conditional on the following known predictors of creatinine concentrations that were associated with creatinine in our study population: maternal age, race/ethnicity, education, pre-pregnancy BMI, and height.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion of age, gender, race/ethnicity, and other factors in addition to UCR concentration as independent variables allows the models to analyze a variance-covariance matrix of these independent variables and how the observed levels of the analyte of interest used as a dependent variable are affected by inter-dependencies of these independent variables. Thus, based on the mathematical logic, it seems that the model-based method of creatinine correction should be a method of choice as has also been recommended by Barr et al (2005) andO'Brien et al (2016). In order to do a complete, valid, and reliable model-based creatinine-corrected analysis, it is almost essential that variables representing all factors that affect and may affect both UCR and the analyte of interest be included in the model as independent variables.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, within the context of being able to predict an event of interest, from the observed values of urinary analyte concentrations, O'Brien et al (2016) evaluated the efficacy of seven different statistical modeling approaches under three different scenarios, namely, (i) when UCR is affected by hydration only; (ii) when UCR is affected by hydration as well as other factors like age, gender, race/ethnicity, etc., which in turn may also affect the probability of the occurrence of the event of interest; and (iii) when UCR is affected by hydration as well as other factors like age, gender, race/ethnicity, etc., which in turn may also affect the probability of the occurrence of the event of interest and the magnitude of environmental exposure. Almost uniformly, based on the results of several simulation studies with different known probabilities of the occurrence of the event, O'Brien et al (2016) was found to correctly predict the probability of the event of interest more often when UCR and other factors that can be considered to affect the probability of the event of interest are used as independent variables in regression models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation